Age-Related Impairment of Pancreatic Beta-Cell Function: Pathophysiological and Cellular Mechanisms - De Tata, Vincenzo (Frontiers in Endocrinology, 2014)
The incidence of type 2 diabetes significantly increase with age. The relevance of this association is dramatically magnified by the concomitant global aging of the population, but the underlying mechanisms remain to be fully elucidated. Here some recent advances in this field are reviewed, at the level of both the pathophysiology of glucose homeostasis and the cellular senescence of pancreatic islets. Overall, recent results highlight the crucial role of beta-cell dysfunction in the age-related impairment of pancreatic endocrine function and delineate the possibility of new original therapeutic interventions .